Outpatient treatment of alcohol use disorders among subjects 60+ years: design of a randomized clinical trial conducted in three countries (Elderly Study) - Andersen, Kjeld (BMC Psychiatry, 2015)
BACKGROUND: The proportion of 60+ years with excessive alcohol intake varies in western countries between 6–16 % among men and 2–7 % among women. Specific events related to aging (e.g. loss of job, physical and mental capacity, or spouse) may contribute to onset or continuation of alcohol use disorders (AUD). We present the rationale and design of a multisite, multinational AUD treatment study for subjects aged 60+ years. METHODS/DESIGN: 1,000 subjects seeking treatment for AUD according to DSM-5 in outpatient clinics in Denmark, Germany, and New Mexico (USA) are invited to participate in a RCT. Participants are randomly assigned to four sessions of Motivational Enhancement Treatment (MET) or to MET plus an add-on with eight sessions based on the Community Reinforcement Approach (CRA), which include a new module targeting specific problems of older adults. A series of assessment instruments is applied, including the Form-90, Alcohol Dependence Scale, Penn Alcohol Craving Scale, Brief Symptom Inventory and WHO Quality of Life. Enrolment will be completed by April 2016 and data collection by April 2017. The primary outcome is the proportion in each group who are abstinent or have a controlled use of alcohol six months after treatment initiation. Controlled use is defined as maximum blood alcohol content not exceeding 0.05 % during the last month. Total abstinence is a secondary outcome, together with quality of life andcompliance with treatment. DISCUSSION: The study will provide new knowledge about brief treatment of AUD for older subjects. As the treatment is manualized and applied in routine treatment facilities, barriers for implementation in the health care system are relatively low. Finally, as the study is being conducted in three different countries it will also provide significant insight into the possible interaction of service system differences and related patient characteristics in predictionof treatment outcome. TRIAL REGISTRATION: Clinical Trials.gov NCT02084173, March 7, 2014.